Na-doped ruthenium perovskite electrocatalysts with improved oxygen evolution activity and durability in acidic media - María Retuerto (Nature Portfolio, 2019)
While water splitting may afford a renewable means to store energy in chemical bonds, water oxidation catalysts suffer from poor stabilities in acidic media. Here, authors show sodium doping of strontium ruthenate to improve the catalytic durability while maintaining a high O2 evolution activity.